Staff perception on customer choice of stay case of Shangri-La Rasa Ria Resort Tuaran / Emmylen Pius - Pius, Emmylen (2013)
Tourism has become one of the importance industries in Sabah, Malaysia. With the existence of the Mount Kinabalu known worldwide as the highest mount in Asia, adding the land nature and environment has attracted many tourists to come in these days. Today, with the growing capacity of tourist's entry to Sabah, the resort and hotel of stay also expanding. Among all resort in Sabah, Shangrila Rasa Ria Resort has leading the ranks and of course with the highest ranks come with the best offers. Instead of other resort and hotel in Kota Kinabalu, the tourist chose Shangri-la Rasa Ria Resort as their main option. From this point, the issue has intrigued the researcher mind that even the resort offer the highest rates, people are keep coming and most of them are European, Japanese, Chinese and middle east country people. This research is conducted to find out the main point or purpose for tourist to come in Shangri-la Rasa Ria Resort and to find out how the company improve their performance for better future.